THE EFFECT OF ADDING MICROORGANISMS TO THE COMPRESSION OF PALEMBANG PEAT SOIL - Hayati, Julita
Peat soil is one of the problematic land which has high compressibility and water content. Peat soil also has a low bearing capacity so that improvements need to be made to increase the bearing capacity of peat soil. Peat soil from Banyu Asin Regency Palembang is a type of fibrous peat soil with a fairly low water content. The level of decomposition of peat soils is quite high, this is indicated by the condition of degraded peatlands. The organic matter contained is also high. The use of peat land as the basis for construction is feared to have a large decline due to the construction burden on it. This research was conducted to study the effect of adding microorganisms to the compression of peat soil. The microorganisms used came from decomposers, Bios 44. Based on the results of the analysis, the addition of microorganisms with variations of 5%, 10% and 15% on peat soil affects the compression and density. The density of peat soil increases with the large percentage of addition of microorganisms contained in Bios 44. This is indicated by the increase in dry weight and the decrease in the optimum water content of peat soil samples. The increase in the largest dry weight occurred at the addition of 15% Bios 44 which was equal to 1.09 gr / cm3. The decrease in mixed peat soils decreases with the increase in the percentage of Bios 44. The percentage decrease in initial peat soil is 15.56% while for peat soil samples with 15% Bios 44 the percentage decrease is 10.24%. Compression that occurs is reduced to 5% of the total decrease in initial peat soil. Increased CaCO3 content in peat soil causes the pore cavity to decrease so that the resulting compression decreases. Therefore Bios 44 can be used as an alternative to improve the parameters of peat so that it can be used as a construction subgrade.